Managing educational institutions: School heads’ leadership practices and teachers’ performance - Cherry Joy C. Aquino; Bonimar T. Afalla; Fitzgerald L. Fabelico (Institute of Advanced Engineering and Science, 2021)
School heads are agents of change who contribute a major impression on the educational milieu through their information-sharing methods, creating supportive social connections, participating in mentoring programs, and fostering progress. Hence, this study ascertained the interrelation between the public school head’s leadership practices and teachers’ performance. As correlation research, simple random sampling was used to calculate the sample size for teachers, while total enumeration was used for school heads. A structured questionnaire was developed to gather the necessary information that reinforced the theme of this analysis. Weighted mean was used to ascertain the level of leadership practices of school heads and the level of teacher performance. T-test, F-test, post-hoc test, and Pearson r were employed to establish the degree of association between and among variables. This study concluded that the variation in leadership practices experienced by school heads and teachers is absolutely vital, confirming that their reactions are fundamentally better. Teachers' performance is consistent irrespective of age, educational achievement, or significant contributions. In terms of teaching status and number of years of experience, head teachers have improved teaching efficiency than teachers and master teachers. Teachers with shorter relevant experience showed poorer educational quality relative to those who spent more time in the school system. School heads who have obtained their doctorate degrees get a greater level of leadership practices than the holders of master's degrees. The very productive performance of teachers stays the same, regardless of whether the school heads exhibit a very high degree of authentic leadership.